(untitled) (Bangladesh Journal of Pharmacology, 2014)
We have herein computationally examined binding affinities and specificity of 2-hydroxy-3,5-dinitrobenzamide (HDNB), a small chemical molecular BH3-mimetic identified by means of peptidodynmimetic method, on the BH3-binding grooves of six anti-apoptotic proteins (Bcl-2, Bcl-B, Bcl-W, Bcl-XL, Bfl-1 and Mcl-1) from human beings. The HDNB ligand was found to interact on the BH3-binding grooves of Bcl-2, Bcl-B, Bcl-XL, Bfl-1 and Mcl-1, whereas it did not act as BH3-mimetic to Bcl-W. Moreover, binding affinities of the HDNB towards the anti-apoptotic proteins were significantly different from each other. The differential binding affinities and specificity of the HDNB towards the anti-apoptotic proteins have been chiefly attributed to the differences in the chemical properties of BH3-binding grooves of the proteins. Implications of the study to design efficient de novo antagonists to the anti-apoptotic proteins using the HDNB as seed molecule have been discussed.